The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1017/s0033291707001390
|View full text |Cite
|
Sign up to set email alerts
|

Co-morbidity and disorder-related distress and impairment in purging disorder

Abstract: PD is associated with elevated distress and impairment and should be considered for inclusion as a provisional disorder in nosological schemes such as the Diagnostic and Statistical Manual to facilitate much-needed research on this clinically significant syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 29 publications
5
67
2
Order By: Relevance
“…However, women with PD reported lower eating concerns, had lower scores on the Three Factor Eating Questionnaire Hunger and Disinhibition scales, and had lower depression and trait anxiety as well as lower rates of current mood disorders compared to women with BN. 8 These findings have been largely replicated in a third study by Keel et al 9,10 In addition, Keel et al 10 found comparable impairment in BN and PD and higher rates of current anxiety disorders in PD compared with BN in their third study. In a sample of treatment-seeking adolescents, Binford and le Grange 11 found no significant differences between PD and BN on measures of dietary restraint, depression, or lifetime diagnoses of depressive disorder, anxiety disorder, or substance use.…”
Section: Clinical Significance Of Pdmentioning
confidence: 83%
See 3 more Smart Citations
“…However, women with PD reported lower eating concerns, had lower scores on the Three Factor Eating Questionnaire Hunger and Disinhibition scales, and had lower depression and trait anxiety as well as lower rates of current mood disorders compared to women with BN. 8 These findings have been largely replicated in a third study by Keel et al 9,10 In addition, Keel et al 10 found comparable impairment in BN and PD and higher rates of current anxiety disorders in PD compared with BN in their third study. In a sample of treatment-seeking adolescents, Binford and le Grange 11 found no significant differences between PD and BN on measures of dietary restraint, depression, or lifetime diagnoses of depressive disorder, anxiety disorder, or substance use.…”
Section: Clinical Significance Of Pdmentioning
confidence: 83%
“…Compared with noneating disordered controls, women with either current 8 or lifetime PD 14,15 report significantly greater depression, 8,15 anxiety, 8,15 higher rates of Axis I and II disorders, 8,15 greater impairment in psychosocial function, 10,14 and higher suicidality. 15 Using the DSM-IV conceptualization of clinical significance, PD is a mental disorder based on present distress, impairment in one or more important areas of function, and increased risk of suffering death, pain, or disability.…”
Section: Clinical Significance Of Pdmentioning
confidence: 92%
See 2 more Smart Citations
“…2,7 A more consistent pattern has emerged when looking at anxious personality traits, with studies finding greater trait anxiety in women with BN compared to women with PD. 7,10 Importantly, the relatively small number of participants in studies comparing BN and PD may have limited statistical power for detecting differences, particularly for analyses based on personality disorder diagnoses. Indeed, studies utilizing continuous measures of personality pathology have been more likely to yield significant differences between PD and BN.…”
Section: Introductionmentioning
confidence: 99%